Communicating conservation: how do the Nepalese print media portray caterpillar fungus? An analysis of newspaper coverage from 2008–2021. Issue 9 (September 2022) - Poudel, Sanjeev; Shrestha, Uttam Babu; Pandit, Ram; Dhital, Krishna Ram
Abstract: Caterpillar fungus ( Ophiocordyceps sinensis ) makes an economically important contribution to livelihoods of the local people in the Himalaya. Its extraordinarily high market price as an aphrodisiac, and pressure in the natural habitats due to overharvesting and climate change, have attracted local and global media attentions. Despite the wide media coverage on various social and environmental aspects of the caterpillar fungus, a consolidated analysis of the news and featured articles about the different dimensions of the caterpillar fungus is lacking. In this paper, we assess how the Nepalese print media have portrayed the social, economic, governance, and biological dimensions of caterpillar fungus conservation and management. We conducted a thematic analysis of newspaper articles published for fourteen years from 2008–2021 in seven national daily newspapers in Nepal. We used an inductive method to extract the keywords from the printed newspapers, resulting in 3, 777 keywords from 681 news items belonging to eight thematic areas. Based on the similarities and differences in the keywords, the news items were categorized into eight themes: impacts of caterpillar fungus harvesting (28% news coverage), trade of caterpillar fungus (16%), general information about the fungus (15%), harvesting of the fungus (14%), governance mechanisms (14%), challenges to the harvesters (6%), policy gaps (4%), and institutional and policy responses (3%). We found that Nepalese media highlighted the socio-economic and environmental impacts of caterpillar fungus harvesting but presented less information about the government response to its conservation, gaps in knowledge and governance mechanisms necessary to conserve the fungus. The thematic analysis of media reporting can help in devising long term conservation and management policies of the caterpillar fungus, particularly focussing on the issues frequently reported by the national media. Abstract : Caterpillar fungus, Conservation, Nepal, Newspaper, Media, Thematic analysis.